2019
DOI: 10.1371/journal.pone.0223621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of SAND battery to evaluate language in patients with Progressive Supranuclear Palsy

Abstract: BackgroundProgressive Supranuclear Palsy (PSP) patients present language disturbances in tasks like naming, repetition, reading, word comprehension and semantic association compared to Parkinson’s disease (PD) and healthy controls (HC).ObjectiveIn the present study we sought to validate a Screening for Aphasia in NeuroDegeneration (SAND) battery version specifically tailored on PSP patients and to describe language impairment in relation to PSP disease phenotype and cognitive status.Methods and resultsFifty-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…We found that the MSA-tailored SAND Global Score, composed of 17 tasks, is an acceptable, reliable and easily applicable tool to explore language profile in MSA patients. By removing sub-scores with high proportion of missing values, we obtained a significant improvement in consistency and acceptability comparable with the original SAND Global Score and PSP-tailored SAND (Battista et al 2005 ; Picillo et al 2019 ).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We found that the MSA-tailored SAND Global Score, composed of 17 tasks, is an acceptable, reliable and easily applicable tool to explore language profile in MSA patients. By removing sub-scores with high proportion of missing values, we obtained a significant improvement in consistency and acceptability comparable with the original SAND Global Score and PSP-tailored SAND (Battista et al 2005 ; Picillo et al 2019 ).…”
Section: Discussionsupporting
confidence: 54%
“…In this study, we evaluated an often overlooked aspect of cognitive dysfunction in movement disorders, namely language impairment. Indeed, a growing number of studies, especially regarding idiopathic PD, reported significant difficulties with language tasks, including understanding of sentences, verbal fluency and naming (Picillo et al 2019;Catricalà et al 2013Catricalà et al , 2019. Generally, language alterations have also been reported in patients with lesions of the basal ganglia following stroke (Auclair-Ouellet et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific deficits comprising non-fluent aphasia in PSP/CBS include simplified or agrammatic speech produced in an effortful manner, with impaired grammatical comprehension and preserved lexical comprehension; and often accompanied by Apraxia of Speech. A version of the Screening for Aphasia in Neurodegeneration battery has been used for PSP patients and proposed as a reliable tool to screen for these characteristic language disturbances (180). For treatment of speech apraxia in PSP, one recent study (181) provides Class III evidence that transcranial direct current stimulation over the dorsolateral prefrontal cortex improves performance in some language tasks, but more study is required.…”
Section: Non-fluent Aphasiamentioning
confidence: 99%
“…Such tasks might disadvantage PSP patients due to their oculomotor abnormalities or disadvantage both PSP and CBS patients due to motor deficits. This complicates interpretation of results from investigations of language in these disorders because scoring is often binary, the reasons for task failures can be unclear and can differ across disorders (Peterson et al, 2019 ; Picillo et al, 2019 ). The MLSE addresses this longstanding issue by incorporating an error-based scoring system to capture language-specific contributions to impaired test performance, enabling one to tease apart linguistic deficits from one another and from other impairments.…”
Section: Discussionmentioning
confidence: 99%